2013
DOI: 10.1186/1743-422x-10-52
|View full text |Cite
|
Sign up to set email alerts
|

An attenuated Lassa vaccine in SIV-infected rhesus macaques does not persist or cause arenavirus disease but does elicit Lassa virus-specific immunity

Abstract: BackgroundLassa hemorrhagic fever (LHF) is a rodent-borne viral disease that can be fatal for human beings. In this study, an attenuated Lassa vaccine candidate, ML29, was tested in SIV-infected rhesus macaques for its ability to elicit immune responses without instigating signs pathognomonic for arenavirus disease. ML29 is a reassortant between Lassa and Mopeia viruses that causes a transient infection in non-human primates and confers sterilizing protection from lethal Lassa viral challenge. However, since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 50 publications
1
49
0
2
Order By: Relevance
“…Although it was easier to isolate ML29 virus from SIV-infected macaques, the viremia and levels of ML29 remained transient and low (15). Given the attenuated nature of ML29, those animals did not show increased signs of pathology or shortened life spans due to the SIV infection; however, they did show both humoral and cell-mediated immune responses to LASV GP and NP similar to those of non-SIV-infected animals (15).…”
Section: Discussionmentioning
confidence: 98%
“…Although it was easier to isolate ML29 virus from SIV-infected macaques, the viremia and levels of ML29 remained transient and low (15). Given the attenuated nature of ML29, those animals did not show increased signs of pathology or shortened life spans due to the SIV infection; however, they did show both humoral and cell-mediated immune responses to LASV GP and NP similar to those of non-SIV-infected animals (15).…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, significant efforts aimed at developing safe and effective vaccines against HFAs have been made (15,39). The Mopeia virus/LASV reassortant ML29 is a promising LASV LAV candidate (40). However, although the genetic differences that distinguish ML29 from the pathogenic LASV are known, the mechanisms of ML29 attenuation remain unknown, which raises concerns about the phenotypic stability of ML29 in response to additional mutations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that use of NP, GPC or the 2 G proteins or a combination of NP/GPC is protective in a variety of animal models. 10,14,15,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Studies of convalescent sera from patients with Lassa Fever or human HLA transgenic mice identified a number of epitope targets within the NP, GP1, GP2 and GS proteins. 11,12,16,19,[57][58][59][60][61][62][63] Recent work in a guinea pig model utilizing the GP1 and GP2 proteins in a DNA vaccine resulted in adequate protection from challenge virus.…”
Section: Discussionmentioning
confidence: 99%